Ex situ conservation of wild ornamental plants at JNTBGRI - Kumar, E S Santhosh; Vikraman, R Raj; Raj, M P Jithin; Prakashkumar, R (Indian Horticulture, 2019)
Wild ornamental plants are one of the untapped resources of the Western Ghats. In the present paper, nearly 300 species of underexploited or unexploited plants conserved at JNTBGRI are presented here along with their botanical identity, family, ornamental attraction, gardening or landscape application, propagation methods, etc. for their easy identification.